The Effect of Profitability, Firm Size and Growth Opportunity On The Value of Manufacturing Companies Listed On The Indonesia Stock Exchange In 2017-2020 - Gulo, Meidama; Lady Sivera, Dica (Fakultas Ekonomi, Universitas Ekasakti, 2024)
This study discusses the effect of profitability, firm size and growth opportunity on firm value in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2017-2020. Data processing in this research is using multiple regression model. The source of data in this study is secondary data obtained indirectly from data obtained from the company's annual financial report published on the Indonesia Stock Exchange website. The sample taken in this study used a purposive sampling technique. The results of the analysis of this study indicate that the profitability (ROA) variable partially has a significant effect on firm value (PBV) with a significance (0.016 <0.05). Firm size variable partially has no effect on firm value (PBV) with a significance (0.164 > 0.05, growth opportunity variable partially has a significant effect on firm value (PBV) with a significance (0.000 < 0.05). Simultaneous f test results profitability, firm size and growth opportunity simultaneously affect firm value (significantly 0.000 < 0.05).